Global and regional trends in the nutritional status of young people: a critical and neglected age group. Issue 1 (April 2017) - Akseer, Nadia; Al‐Gashm, Sara; Mehta, Seema; Mokdad, Ali; Bhutta, Zulfiqar A.
Abstract : Adolescence and emerging adulthood form a critical time period for the achievement of optimal health and nutrition across all stages of the life course. We undertook a review of published literature and global data repositories for information on nutrition levels, trends, and patterns among young people aged 10–24 years from January 1, 2016 to September 20, 2016. We describe patterns for both males and females at the global level and for geographic regions for the period covering 1990–2015. The results of this study paint a less than ideal picture of current young people's nutrition, suggesting dual burdens of underweight and high body‐mass index in many countries and variable improvements in micronutrient deficiencies across geographical regions. Poor diet diversity and lack of nutrient‐dense food, high risk for metabolic syndrome, and sedentary lifestyles also characterize this population. The need for objective, comparable, and high‐quality data is also recognized for further study in this area. As the global community works toward supporting and scaling up health gains in the sustainable development goal era, realizing the critical role of young people is essential. Investing in young people's nutrition is critical to making strides in improving the overall health and well‐being of all populations.